Term Structure of Credit Spreads of A Firm When Its Underlying Assets are Discontinuous - Surya, Budhi Arta (The Asian Journal of Technology Management (AJTM), 2010)
We revisit the previous works of Leland [12], Leland and Toft [11] andHilberink and Rogers [7] on optimal capital structure and show that thecredit spreads of short-maturity corporate bonds can have nonzero valueswhen the underlying of the firm’s assets value has downward jumps. We givean analytical treatment of this fact under a general Levy process and discusssome numerical examples under pure jump processes.Keywords: Optimal capital structure, credit risk, term structure of creditspread